Produção otimizada de 1,3-propanodiol, ácido propiônico, etanol e hidrogênio, a partir de glicerol bruto e cultura mista, em reator anaeróbio de leito fluidificado - Paranhos, Aline Gomes de Oliveira (2016)
This study aimed to optimize the production of hydrogen and other metabolites using crude glycerol as substrate, through design of experiments (DoE) and statistical process optimization. The first study aimed at optimizing the operational parameters of the fermentation process, and therefore, a mesophilic AFBR reactor was operated on 10 different phases, distributed as a combination of HRT and the glycerol concentration (Gc) proposed by a matrix containing CCD array containing 10 experimental trials. The HRT varied to 9.24h to 0.76h, while Gc ranged from 17.1g / L to 2.9 g / L. The results showed that the maximum conversion of glycerol (CG), 98.4%, was obtained using substrate concentrations lower than 5.0 g/L. The maximum yield (0.17 mol H2 / mol consumed glycerol) and H2 content in the produced biogas (87.4%) were achieved at concentrations greater than 10.0 g/L and HRT of 5h. Among the main soluble metabolites produced, 1,3-propanediol (1,3-PD) and propionic acid (HPr) stood out. The maximum yield of 1,3-PD (1.05 mol 1,3-PD / mol consumed glycerol) was obtained with 10.0 g/L glycerol in HRT of 9,24h, whereas the maximum yield of HPr (0.71 mol HPr / mol consumed glycerol) was achieved with 15.0 g/L of glycerol and HRT of 2h. The second study, in turn, consisted of optimizing the culture medium components (glycerol, KH2PO4, yeast extract and vitamin B12), through batch tests, and subsequent application in AFBR reactor. The maximum hydrogen and ethanol yields, 0.006 and 0.291 mol / mol consumed glycerol, was obtained in optimal culture medium consisting of 26.53 g/L glycerol, 1.75 g/L KH2PO4, 0.0076 g/L B12 and 0.5 g/L yeast extract. The application of optimal culture medium in a continuous reactor did not result in improvement of H2 and ethanol yields, however, caused an increase in 1,3-PD yield, reaching a maximum of 0.38 mol 1.3-PD / mol consumed glycerol.